Structural and electrical properties of K-doped Sr1.85Ca0.15NaNb5O15 lead-free piezoelectric ceramics. Issue 8 (June 2016) - Yin, R.Q.; Zheng, P.; Wang, J.C.; Dai, B.W.; Zheng, L.M.; Du, J.; Zheng, L.; Deng, J.X.; Song, K.X.; Qin, H.B.
Abstract: Lead-free piezoelectric ceramics Sr1.85 Ca0.15 Na1− x K x Nb5 O15 (0.00≤ x ≤0.40) were prepared using the conventional solid state reaction method. The structural, dielectric and piezoelectric properties were systematically studied. All the ceramics are single orthorhombic tungsten bronze phase at room temperature, and the lattice constants increase with K + content. The dielectric spectra of each composition had two dielectric anomalies. The Curie temperature T c gradually decreases from 291 °C to 266 °C as x increase from 0.00 to 0.40, and the transition temperature Ts from orthorhombic phase to tetragonal phase increases from 39 °C to 109 °C. With increasing K + contents, the piezoelectric coefficient d 33 increases rapidly initially, reaches a maximum and then gradually decreases. The highest piezoelectric performance was obtained at x =0.10, with piezoelectric coefficient d 33 =114 pC/N. Mechanisms that lead to the enhancement of d 33 were discussed from the viewpoint of polarization and crystal structure.